2021
DOI: 10.1038/s41467-021-23853-y
|View full text |Cite
|
Sign up to set email alerts
|

Source sector and fuel contributions to ambient PM2.5 and attributable mortality across multiple spatial scales

Abstract: Ambient fine particulate matter (PM2.5) is the world’s leading environmental health risk factor. Reducing the PM2.5 disease burden requires specific strategies that target dominant sources across multiple spatial scales. We provide a contemporary and comprehensive evaluation of sector- and fuel-specific contributions to this disease burden across 21 regions, 204 countries, and 200 sub-national areas by integrating 24 global atmospheric chemistry-transport model sensitivity simulations, high-resolution satellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
251
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(267 citation statements)
references
References 65 publications
15
251
0
1
Order By: Relevance
“…Fuel consumption for power generation, industrial processes, transportation (including airplanes, shipping, and heavy-, medium-, and light-duty vehicles), agriculture, and residential energy use (e.g., heating, cooking, and lighting), releases CO 2 and a mixture of air pollutants (e.g., black carbon, organic carbon), and air pollution precursor emissions (e.g., nitrogen oxides, volatile organic compounds, sulfur dioxide) that form secondary pollutants like fine particulate matter (PM 2.5 ) and ozone. Globally, over half of the PM 2.5 mortality burden is attributable to coal combustion (McDuffie et al, 2021). Emissions from residential, industrial, and energy sectors contribute an estimated 19, 12, and 10% of global PM 2.5 mortality.…”
Section: Air Qualitymentioning
confidence: 99%
“…Fuel consumption for power generation, industrial processes, transportation (including airplanes, shipping, and heavy-, medium-, and light-duty vehicles), agriculture, and residential energy use (e.g., heating, cooking, and lighting), releases CO 2 and a mixture of air pollutants (e.g., black carbon, organic carbon), and air pollution precursor emissions (e.g., nitrogen oxides, volatile organic compounds, sulfur dioxide) that form secondary pollutants like fine particulate matter (PM 2.5 ) and ozone. Globally, over half of the PM 2.5 mortality burden is attributable to coal combustion (McDuffie et al, 2021). Emissions from residential, industrial, and energy sectors contribute an estimated 19, 12, and 10% of global PM 2.5 mortality.…”
Section: Air Qualitymentioning
confidence: 99%
“…In highly urbanized regions, the environmental concentration of Arsenic (As), cadmium (Cd), lead (Pb), and black carbon (BC) is high (56). PM2.5 is the mass of particles per cubic meter in the air, with a size (diameter) generally <2.5 micrometers (µm), and is well-known as delicate particulate matter (2.5 micrometers is one 400th of a millimeter) (57). Studies have found that PM2.5 and BC were positively associated with an osteoporosis-related fracture (58).…”
Section: Discussionmentioning
confidence: 99%
“…This global burden, however, is not uniformly distributed across all countries, with air pollution-attributable mortalities generally much higher in low to middle income countries (generally upper right in Figure 2). The main sources of air pollution in each region differ as well (McDuffie et al, 2021). A much larger fraction of pollutant emissions in lower income countries originate from solid biofuel use and open burning, while sources shift to predominantly fossil fuel combustion in high Socio-Demographic Index (SDI) countries (GBD 2019Risk Factor Collaborators, 2020.…”
Section: Impactsmentioning
confidence: 99%